FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA PERUSAHAAN INDEKS LQ45 DI BURSA EFEK INDONESIA (BEI) PERIODE 2020-2023) - Arli Mandala Putra; Nensi Yuniarti. Zs; Budi Astuti; Chairul Suhendra (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the effect of profitability, liquidity, leverage, and sales growth on tax avoidance with Good Corporate Governance as a moderating variable in companies included in the LQ45 Index on the Indonesia Stock Exchange (IDX) for the 2020–2023 period. Tax avoidance is proxied by the Effective Tax Rate (ETR), profitability is measured using Return on Assets (ROA), liquidity using the Current Ratio (CR), leverage using the Debt to Equity Ratio (DER), sales growth is measured based on sales growth, and Good Corporate Governance is proxied by institutional ownership. This study uses a quantitative approach with secondary data obtained from financial statements and company annual reports. The sampling technique uses a purposive sampling method to obtain 168 observational data. The data analysis methods used are multiple linear regression and Moderated Regression Analysis (MRA). The results show that partially profitability, liquidity, and sales growth do not have a significant effect on tax avoidance, while leverage has a significant effect on tax avoidance. Simultaneously, profitability, liquidity, leverage, and sales growth have a significant effect on tax avoidance. Furthermore, good corporate governance (GCG) was unable to moderate the effects of profitability, liquidity, and sales growth on tax avoidance, but it was able to moderate the effect of leverage on tax avoidance. This finding indicates that a company's funding structure, controlled by good corporate governance, plays a significant role in influencing tax avoidance practices in LQ45 companies. Keywords: Tax Avoidance, Profitabilitas, Likuiditas, Leverage, Sales Growth, Good Corporate Governance